Kontribusi Kepemimpinan Kepala Sekolah terhadap Produktivitas Publikasi Ilmiah Guru SMA - Jamaludin, Jamaludin; Trisoni, Ridwal; Herlina, Elda; Erlinda, Rita; Demina, Demina (STKIP PGRI SITUBONDO, 2024)
The role of teachers in education is very strategic as the spearhead of the implementation of education in shaping human resources. To carry out this task, teachers must have various competencies, including pedagogical, personality, social and professional competencies. One indicator of a professional teacher is the ability to make scientific publications. Unfortunately, the number of teachers who can make scientific publications still need to be increased. This study aims to determine the contribution of principal leadership and information literacy skills to the productivity of scientific publications of high school teachers in Limapuluh Kota Regency. The type of research used is correlation research using a quantitative approach. This study involved high school teachers as respondents. Data were collected through research instruments in the form of questionnaires focusing on teachers’ perceptions of principal leadership, information literacy skills, and scientific publication productivity. Data analysis techniques including basic assumption test, classical assumption test, and hypothesis testing were conducted to determine: 1) the contribution of leadership to teacher scientific publication productivity; 2) the contribution of information literacy skills to teacher scientific publication productivity; 3) the contribution of principal leadership together with information literacy skills to teacher scientific publication productivity with simple regression and multiple regression. The research results showed: 1) there is a positive correlation between the principal's leadership and the productivity of teachers' scientific publications with a pearson correlation value of 0.317 and a significance of 0.000 (0.000 < 0.05) with a low degree of relationship criteria; 2) there is a significant contribution between teachers' information literacy skills to the productivity of teachers' scientific publications with a pearson correlation value of 0.228 with low criteria and a significance of 0.009 (0.009, 0.05); Principal leadership and teachers' information literacy skills together simultaneously contribute to the productivity of teachers' scientific publications with a significance value for the effect of principal leadership on the productivity of teachers' scientific publications of 0.002 (0.002, 0.05) and the value of t count = 3.108 (t count> t table 1, 979), and the significance value of the effect of teachers' information literacy skills on the productivity of scientific publications of 0.011 (0.011 < 0.05) and the value of t count = 2.653 > t table 1.979.